Performance time of anesthesiology trainees for cricothyroid membrane identification and characteristics of cricothyroid membrane in pediatric patients using ultrasonography. Issue 7 (7th April 2022) - Cho, Sung‐Ae; Kang, Pyoyoon; Song, In‐Sun; Ji, Sang‐Hwan; Jang, Young‐Eun; Lee, Ji‐Hyun; Kim, Jin‐Tae; Kim, Hee‐Soo; Kim, Eun‐Hee
Abstract: Background: Identifying the cricothyroid membrane is an essential technical skill for front‐of‐neck access procedures. Aims: This study evaluated the usefulness of cricothyroid membrane identification in pediatric patients using ultrasonography by anesthesiology trainees without experience in airway ultrasound and collected anatomical data on the cricothyroid membrane and its surrounding airway structures in children. Methods: This prospective observational study included children aged <18 years scheduled to undergo general anesthesia and anesthesiology trainees who identified the cricothyroid membrane in five sequential anesthetized patients using ultrasonography. A pediatric anesthesiologist confirmed the accuracy of the identified cricothyroid membrane and recorded the performance time. The primary aims were the cricothyroid membrane identification success rate and performance time. The secondary aims were the characterization of the cricothyroid membrane and its surrounding structures. Results: Overall, 150 pediatric patients and 30 anesthesiology trainees were analyzed. The cricothyroid membrane identification success rate using ultrasonography was 100% in all the attempts using a transverse approach. The mean (standard deviation) performance time was 27.2 (18.6) s and 31.0 (23.8) s using the transverse and longitudinal approaches, respectively. The performance time decreased by 3.1 ( p  = .003, 95% confidence interval [CI] = −5.1–−1.0) and 5.2 ( p  = .007, 95% CI = −8.9–−1.4) seconds per increase in number of attempts with the transverse and longitudinal approaches, respectively. The cricothyroid membrane length was mostly correlated with the patients' height ( r  = .75, p  < .001), and the blood vessels surrounding the cricothyroid membrane were observed in 95.9% of the patients. Conclusions: Anesthesiology trainees without experience in airway ultrasound successfully identified the cricothyroid membrane in pediatric patients using ultrasonography after a brief training period. Further research is required as the identification of a structure does not predict the success of the actual procedure, particularly if done in an emergency situation.